Discovering the Determinants of Successful Money Management in Married Women: A Qualitative Study Based on the Grounded Theory - Asadi, Kobra; Yousefi, Zahra; Mahdad, Ali (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to discover determinants of successful money management in married women. methods: The research was conducted with a qualitative method using the grounded theory. Participants were selected by a purposive sampling method and 14 married women were finally interviewed with the semi-structured method until the theoretical saturation, and the results were analyzed using a method by Brown and Clark (2006). Results: In the study, 10 core categories, 26 organizing categories, and 88 primary codes were extracted. The results indicated that the roles of women in successful money management in the family included ten core categories, namely cost reduction, cost prioritization, financial agreements, financial budgeting, more earning, financial empathy, financial education, financial foresight, effective characteristics in money management, and effective communication in financial growth. Conclusion: Family financial management is an important dimension of marital life, and the women's role is important in this management; hence, the effect of women in successful money management is critical in today's families.